Characteristics of Butterfly Pea Flower Klepon with the Addition of Cinnamon Powder (Cinnamomum verum) - Firdaus Paulus Harapan Jaya Pasaribu; Putu Ari Sandhi Wipradnyadewi; Tri Saina Sihotang; Rachel Monica; Lilalita Dian Ayu Fitriyani; Ni Putu Okta Diana Dewi; Ni Made Elza Diah Sastyari (Indonesian Journal of Food Technology, 2026)
Background: Klepon is a traditional snack made from glutinous rice flour with brown sugar filling and has a small green round shape. The brown sugar flavor dominates so it is considered monotonous and the green color is from synthetic dyes so it is considered harmful to health. Cinnamon has a distinctive flavor and can act as an antioxidant, while butterfly pea flowers contain anthocyanins that can act as natural dyes and have antioxidant activity. Purpose: This study aims to determine the effect of adding cinnamon powder on sensory characteristics, antioxidant activity, total reducing sugars, and texture of butterfly pea flower klepon. Method: This research method used an experimental method with a completely randomized design (CRD), namely the addition of cinnamon powder concentrations to the klepon filling of 0, 5, 10, and 15 % (w/w). Result: The results of the study showed that the best hedonic test results were in the treatment of adding 5% cinnamon powder concentration (P1) with an aroma value of 5.56 (like), color 5.73 (like), texture 5.40 (rather like), taste 5.53 (like), and overall acceptance 5.66 (like). Based on the results of the scoring test, it was found that the addition of cinnamon powder had a significant effect (P<0.05) on the aroma and taste of butterfly pea flower klepon. The follow-up test showed that the addition of cinnamon powder had a significant effect on antioxidant activity, but no significant effect on the total reducing sugar content of butterfly pea klepon.